The Discounting Confusion: An Ecological Economics Perspective - Müller, Frank G. (2013)
Factors impacting on the discounting process are mirrored in every aspect of human activities, be it the philosophical, the aesthetic, the religious through to the environmental and scientific experiences. In short, discounting is a controversial concept, and yet, the economic profession seems to ignore that issues related to “long-term” discounting are complex, multifaceted, and far from settled. The environmental community in particular has expressed reservations about discounting, because this process —an inherently myopic one— embodies a built-in bias against the future generations.It will be argued here that the danger to ecological sustainability is of a specific nature, namely,it relates to the lack of substitutability between human-made capital and natural capital. If this assumption is accepted, then it follows that using a discount rate is an inadequate instrumentfor achieving sustainability. Thus, it will be argued that the implementation of the precautionary principle, e.g., in form of “safe minimum standards” of ecosystem protection, provides a successful approach for achieving sustainability.